Residual Effect of Nutrient Management Practices in Lowland Rice Varieties on Growth, Productivity, Economics and Nutrient Uptake of Succeeding Black Gram in Rice–Black Gram Cropping Sequence - Das, Priyanka; Barik, A. K.; Roul, P. K.; Pattanayak, Sarthak; Nayak, A. K. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted during rabi seasons (December–March) of 2019–20 and 2020–21 to study the residual effect of nutrient management practices in lowland kharif rice varieties on succeeding black gram variety PU 31. The experiment was set in split plot design with four rice varieties in main plots (viz. CR 1009 sub-1, CR 1018, Pooja and Upahar) and six nutrient management practices in sub-plots [(viz. Control, 100% Recommended dose of fertilizers (RDF: 80-40-40 kg N, P2O5, K2O ha-1), 50% RDF+FYM (@ 8 t ha-1), 50% RDF+Sesbania green manuring (@ 1.5 t ha-1), Rice crop manager (115.5 -32.7-52.8- 25.0 kg N, P2O5, K2O, ZnSO4 ha-1+FYM @ 3 t ha-1) and Real time nitrogen management (RDF+customised leaf colour chart (CLCC)] and each treatment was replicated thrice. Among different nutrient management practices in rice, rice crop manager exhibited highest number of pods plant-1 (31.3), seeds pod-1 (7.8), 1000 seed weight (39.6 g), seed yield (877 kg ha-1), haulm yield (2512 kg ha-1), gross return (Rs. 51352 ha-1), net return (`Rs. 38947 ha-1) and return Rs.`-1 invested (`Rs. 4.14) and highest uptake of N (78.83 kg ha-1), P (7.60 kg ha-1) and K (53.09 kg ha-1) in residual black gram. This was at par with 50% RDF+FYM @ 8 t ha-1 and significantly higher than all other nutrient managements in preceding rice. So, nutrient management as per rice crop manger and 50% RDF+8 t FYM ha-1 to the preceding rice crop had significant residual influence in achieving highest yield and economic returns from succeeding black gram in rice-black gram cropping sequence.